Choques a la cuenta corriente de la balanza de pagos: Alguna evidencia para Argentina - Luis N. Lanteri (Atlantic Review of Economics (ARoEc), 2018)
– The aim of this paper is to identify the different shocks that could affect the current account in the argentine case, such as the terms of trade (the Harberger-Laursen-Metzler effect- HLM), supply shocks (productivity), demand shocks (real exchange rate and public consumption /current GDP) and the shocks on the production side of the economy. SVAR models with long-term restrictions and quar terly data covering the period 1994-2018 are used. The results of the impulse-response functions suggest the existence of the HLM effect for this country. Shocks in the terms of trade would initially affect to the current account positively, as the improvements in t he productivity and in the public saving (lower consumption).
Keywords: C3; E62; F32; F41; 330; current account; terms of trade; Harberger-Laursen-Metzler (HLM) effect; productivity; public consumption; SVAR models